Genre, agentivité et performance du corps : la construction d’une rhétorique de l’exceptionnalité féminine dans des biographies spirituelles portugaises du XVIIe–XVIIIe siècles - Helena QUEIRÓS (E-REA)
This article is the result of ongoing work on female body representations through a set of Portuguese devout biographies from the 17th to 18th centuries. Holiness being one of the only socially accepted ways for certain women to gain notoriety and thus pass from the margins to the center of power (in the broad sense, but more precisely religious and political), we will try to understand the place of gender as a social construct on this path of virtues. On the one hand, these portraits of heroic women invite reflection on the notion of feminine holiness; on the other hand, this questioning will be related to the evolution of the very notion of holiness after the Council of Trent. Beyond the essentializing specificities of female excellence, where chastity occupies a prominent place, this article will focus on the authors’ discourse on the virility of nuns, on its methods as well as its meaning. If male discourse serves an ideological purpose focused on feminine fragility, it is also worth highlighting the active part that these nuns take in the construction of these representations insofar as it is their agency that gives substance to discourses made on them.